1997
DOI: 10.1093/ajcn/66.2.304
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of or beta-cyclodextrin addition to potato beneficial effect on glucose metabolism and appetite sensations

Abstract: Functional foods are gaining more and more interest from health scientists. One way to improve the nutritional properties of foods may be to modify the starch component, often included to stabilize the food product. In this study two chemically modified starches-a 1-2% acetylated potato starch and a starch enriched with 2% beta-cyclodextrin-and a native, unmodified potato starch (control) were investigated with regard to 6-h energy expenditure, substrate metabolism, hormone concentrations, and subjective appet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 23 publications
6
32
2
1
Order By: Relevance
“…The fi nding of a reduction in post-prandial glycaemia in the present study is in part in agreement with a previous fi nding of Raben et al [20] , who reported that the addition of 1 g of ␤ -CD to 50 g of potato starch resulted in a fl atter post-prandial glucose response, but no difference in the AUC. In the present study the addition of 2 g of ␣ -CD also fl attened the post-prandial glucose response (not signifi cant), with no signifi cant reduction in the iAUC.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The fi nding of a reduction in post-prandial glycaemia in the present study is in part in agreement with a previous fi nding of Raben et al [20] , who reported that the addition of 1 g of ␤ -CD to 50 g of potato starch resulted in a fl atter post-prandial glucose response, but no difference in the AUC. In the present study the addition of 2 g of ␣ -CD also fl attened the post-prandial glucose response (not signifi cant), with no signifi cant reduction in the iAUC.…”
Section: Discussionsupporting
confidence: 93%
“…In addition to reducing the iAUC for glucose, the higher doses of ␣ -CD also achieved greater satiety, an effect that was also reported by Raben et al [20] following the addition of ␤ -CD to potato starch. The satiating effect of low GI foods is well recognised and may contribute to the weight-loss associated with their consumption by reducing food intake [11,26] .…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…(11) showed that a higher postprandial GIP response to a high-fat meal were seen in women after weight loss compared to normal-weight controls, and the authors suggest that GIP may promote hunger and excessive food intake. Other studies have founded that postprandial GIP response was inversely related to the subsequent feeling of satiety (5,12,13). On the other hand, positive (14) or neutral (9,10,15) correlation between postprandial GIP and satiety were also observed.…”
Section: Introductionmentioning
confidence: 89%